Sosialisasi Harmonisasi Akuntabilitas Perencanaan Keuangan Desa Tahun 2023 (Studi Pada Kantor Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi) - Pramukty, Rachmat (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
This com. service aims to examine of the socialization of the 2023 Village Level Financial Planning Responsibility Harmonization Information System (SIHAPKD) at the Sekarwangi Village Office, Cibadak District, Sukabumi Regency. SIHAPKD is a system that aims to increase accountability and transparency in village level financial planning. This com. service uses a qualitative descriptive method with observation and interview methods. Data collection was carried out through questionnaires and in-depth interviews with stakeholders, participatory observation, and analysis of documents related to the implementation of SIHAPKD. The research results showed that the implementation of SIHAPKD socialization at the Sekarwangi Village Office took place in stages with several challenges. It was found that acceptance and understanding of SIHAPKD by village communities is still limited so further efforts are needed to increase their participation and understanding. Apart from that, technical barriers in understanding and socialization are also obstacles that need to be overcome. However, the socialization of SIHAPKD at the Sekarwangi village office is considered a positive step in increasing accountability and village financial planning. This service provides an overview of the implementation of SIHAPKD socialization at the village level and provides recommendations to increase its effectiveness. The meaning of this service is the importance of increasing awareness and active participation of village communities in monitoring village finances and the need for adequate technical support so that this understanding can be implemented properly.